Sex-specific differences in preclinical models of advanced chronic liver disease and portal hypertension - Peio Aristu-Zabalza; María Andrés-Rozas; Zoe Boyer-Díaz; David P. Al-Adra; Douglas Maya-Miles; Sergi Guixé-Muntet; Anabel Fernández-Iglesias; Jordi Gracia-Sancho (Biology of Sex Differences)
Abstract Background Chronic liver disease is a major health concern, but sex-specific differences in its pathophysiology remain unclear. Preclinical studies have predominantly used male animals, limiting findings' relevance to both sexes. This project aimed to explore sex differences in cirrhosis and portal hypertension (PH) in rats, and to find similarities in human samples for translational relevance. Methods Advanced chronic liver disease (ACLD) was induced in male and female Sprague–Dawley rats using thioacetamide (TAA, 250 mg/kg; 12 weeks) or bile duct ligation (BDL; 28 days). Healthy rats served as controls (n = 11–18/group). We assessed in vivo hepatic and systemic hemodynamic parameters, hepatic microvascular function, and hepatic transcriptomic analyses, including sex-specific differences in cellular composition using gene deconvolution (n = 5/group). Two human sample cohorts were compared to preclinical data for translational insights. Results Both animal models showed PH. TAA males had similar portal pressure (PP) to females (14.2 vs 14.1 mmHg), but BDL males had significantly higher PP than females (14.5 vs 12.5 mmHg; p = 0.003). No differences were observed in hepatic microvascular function. In the BDL model, females had more fenestrae and porosity, and less fibrosis. Transcriptomic analysis revealed that TAA males had dysregulated metabolic pathways, while females had deregulated genes in hormone signaling. In the BDL model, males showed higher deregulation in platelet activation, protein degradation, vesicular transport, and disease-related pathways. Gene deconvolution showed males had a more specialized endothelial phenotype basally, with more changes in endothelial and macrophage phenotypes after injury. In MASLD patients, men had dysregulated metabolic pathways, while women showed deregulation in fibrosis, extracellular matrix, and endocrine regulation. In HBV patients, men had more dysregulation in fibrosis, inflammation, and immune response. Female MASLD patients had more activated hepatic stellate cells, and greater loss of endothelial phenotype compared to men. Conclusions This study highlights sex-dependent molecular differences in the pathophysiology of cirrhosis in two preclinical models. Further research in preclinical and human liver disease is essential to develop safe and effective treatments for ACLD in both sexes.